The Musical Interpretation of Pisaan Lampung: A Novel Approach to Teaching Oral Literature - Hidayatullah, Riyan; Ariyani, Farida; Mazlan, Chamil Arkhasa Nikko (CV ALFA EDU KARYA, 2024)
This study explores the musical interpretation of Pisaan Lampung as an innovative approach to teaching oral literature. Pisaan Lampung, a traditional form of oral literature from Lampung, Indonesia, holds significant cultural value and is enriched with musical elements. However, its musical dimensions should be more utilized in educational settings, limiting its full pedagogical potential. A total of four Pisaan performers were selected for this study. These performers were interviewed and observed in their natural performance settings, emphasizing their musical delivery. The interviews and observations were conducted without introducing any specific musical scales, allowing the researchers to capture the performers' authentic expressions and stylistic nuances. The musical analysis focuses on scale, melody, intonation, expression, dynamics, and central tones. The findings reveal that the musical analysis of the vocal melodies in Pisaan Lampung, directly recorded from its performers, exhibits a pentatonic scale closely resembling the Javanese gamelan scale used in Javanese karawitan. This pentatonic structure underscores the deep-rooted cultural connections between the musical traditions of Lampung and Java, highlighting the shared tonal heritage across these regions. Furthermore, the study identifies an instructional design paradigm that uses the pentatonic scale as the fundamental framework for teaching Lampung oral literature. The scale-based pattern produced by this study provides educators with a practical tool for improving the learning experience and deepening students' connection with Lampung's rich cultural heritage.